Development of mathematics questions in PISA format with number content - Putri Aisyah; Sartika Avrilian; Tara Nurpadillah; Natanael Putera Rasjid Ginting; Ratu Ilma Indra Putri; Elsa Susanti; Ruth Helen Simarmata (Fakultas Tarbiyah dan Ilmu Keguran IAIN Metro, 2026)
The low level of mathematical literacy among Indonesian students is reflected in the average results of PISA 2022, indicating the need to develop PISA-style test instruments. Therefore, this study aims to develop PISA-based questions on numbers that are valid and reliable. The method used is a development study consisting of preliminary and formative evaluation stages. The preliminary stage includes analyzing original PISA questions, student needs, curriculum, and determining the material. The formative evaluation stage includes self-evaluation, expert review, one-on-one, and small group discussions. The format of the questions developed is two multiple-choice questions and four contextual descriptions equivalent to PISA. Content validation was tested qualitatively through expert comments, while quantitative analysis was conducted after testing the questions on six junior high school students in Palembang who were selected purposively. Quantitative analysis includes item validity, reliability, difficulty level, and discriminative power. The research results indicate that the questions are valid and reliable based on content appropriateness, ease of understanding, smooth implementation, and time efficiency. These questions can be used as a training tool to improve students' mathematical abilities in accordance with PISA standards. However, this study has limitations due to the limited sample size and only reaching a small group, so it is recommended that further research be conducted with a larger sample size and up to the field test stage.